THE EFFECT OF E-SERVICE QUALITY, BRAND IMAGE, E-CUSTOMER RELATIONSHIP MANAGEMENT ON E-CUSTOMER SATISFACTION AT GOJEK PADANG - Farell Dwi Aferi; Yulia Hendri Yeni (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
Transportation is a means and infrastructure for the economic development of a country that can encourage the rate of economic growth. Supported by progress and the rapid development of technology, transportation services are also increasingly advancing in the form of technology. Online-based transportation transformation is increasingly being implemented in Indonesia. The purpose of online transportation is to help people avoid traffic jams to get to their destinations quickly and on time. One of the online transportation services in Indonesia is GOJEK. In order to compete with its competitors, GOJEK must improve the quality of e-Service Quality, Brand Image and e-Customer Relationship Management services. This study aims to examine the effect of e-service quality, brand image and e-customer relationship management on e-customer satisfaction by processing research data using SPSS. The sampling technique used purposive sampling with a total sample of 294 respondents. e-service quality affects e-customer satisfaction, brand image affects e-customer satisfaction, e-customer relationship management affects e-customer satisfaction.